The Hot and Energetic Universe: AGN feedback in galaxy clusters and groups - Croston, JH; Sanders, JS; Heinz, S; Hardcastle, MJ; Zhuravleva, I; Bîrzan, L; Bower, RG; Brüggen, M; Churazov, E; Edge, AC; Ettori, S; Fabian, AC; et al. (Athena +, 2013)
Mechanical feedback via Active Galactic Nuclei (AGN) jets in the centres of galaxy groups and clusters is a crucial ingredient in current models of galaxy formation and cluster evolution. Jet feedback is believed to regulate gas cooling and thus star formation in the most massive galaxies, but a robust physical understanding of this feedback mode is currently lacking. The large collecting area, excellent spectral resolution and high spatial resolution of Athena+ will provide the breakthrough diagnostic ability necessary to develop this understanding, via: (1) the first kinematic measurements on relevant spatial scales of the hot gas in galaxy, group and cluster haloes as it absorbs the impact of AGN jets, and (2) vastly improved ability to map thermodynamic conditions on scales well-matched to the jets, lobes and gas disturbances produced by them. Athena+ will therefore determine for the first time how jet energy is dissipated and distributed in group and cluster gas, and how a feedback loop operates in group/cluster cores to regulate gas cooling and AGN fuelling. Athena+ will also establish firmly the cumulative impact of powerful radio galaxies on the evolution of baryons from the epoch of group/cluster formation to the present day.
Keywords: astro-ph.HE; astro-ph.HE; astro-ph.CO